Nanoplasma generation by ultrashort pulse laser - Gonawan, F. N.; Romli, M. M.; M. Zuhan, M. K. N.; Jaya, M. A. T. (UMP, 2022)
Short pulse laser is widely used for plasma generation due to its many advantages. Ultrashort pulse lasers are able to interact within atomic clusters in a short time, as compared with the thermal diffusion time. High focal intensities of radiation can be achieved by short pulse and ultrafast laser to induce nanoplasma. Plasma scale length decreases directly with pulse length, where the fraction of laser energy absorbed is certainly decreased. The dynamics of electrons and ions in nanoplasma strongly depends on: (i) photon energy, (ii) size of the plasma, and (iii) laser fluence. By modifying the exciting intensity, depending on